Association Between Iron Deficiency (With or Without Anemia) and Risk of Heart Failure in Adults: A Meta-Analysis of Observational and Clinical Studies - Rashid, Abdul; Hashim , Hashim Bani; Toma, Tanjeeda Parvin; Elhussain, Awad Rahama Mustafa; Sherazi, Syeda Fatima Andleeb; Omar Elhassab, Salaheldeen Elhassab; Mohammed, Abdalmonim Abdoalrhman (Indus Journal of Bioscience Research, 2025)
Background: Iron deficiency, even without anemia, worsens heart failure outcomes. Its independent role in heart failure progression remains unclear despite growing evidence. Objective: To assess the link between iron deficiency and adverse outcomes in heart failure via a systematic review and meta-analysis. Methods: This meta-analysis adhered to PRISMA guidelines. A comprehensive search of PubMed, Embase, Scopus, and the Cochrane Library was conducted to identify eligible studies evaluating iron deficiency and HF outcomes. Inclusion criteria comprised adult HF patients, iron deficiency defined by ferritin